Stable activity of diabetogenic cells with age in NOD mice: dynamics of reconstitution and adoptive diabetes transfer in immunocompromised mice. Issue 3 (July 2014) - Kaminitz, Ayelet; Mizrahi, Keren; Ash, Shifra; Ben‐Nun, Avi; Askenasy, Nadir
Summary The non‐obese diabetic (NOD) mouse is a prevalent disease model of type 1 diabetes. Immune aberrations that cause and propagate autoimmune insulitis in these mice are being continually debated, with evidence supporting both dominance of effector cells and insufficiency of suppressor mechanisms. In this study we assessed the behaviour of NOD lymphocytes under extreme expansion conditions using adoptive transfer into immunocompromised NOD.SCID (severe combined immunodeficiency) mice. CD4+ CD25+ T cells do not cause islet inflammation, whereas splenocytes and CD4+ CD25− T cells induce pancreatic inflammation and hyperglycaemia in 80–100% of the NOD.SCID recipients. Adoptively transferred effector T cells migrate to the lymphoid organs and pancreas, proliferate, are activated in the target organ in situ and initiate inflammatory insulitis. Reconstitution of all components of the CD4+ subset emphasizes the plastic capacity of different cell types to adopt effector and suppressor phenotypes. Furthermore, similar immune profiles of diabetic and euglycaemic NOD.SCID recipients demonstrate dissociation between fractional expression of CD25 and FoxP3 and the severity of insulitis. There were no evident and consistent differences in diabetogenic activity and immune reconstituting activity of T cells from pre‐diabetic (11 weeks) and new onset diabetic NOD females. Similarities in immune phenotypes and variable distribution of effector and suppressor subsets in various stages of inflammation commend caution in interpretation of quantitative and qualitative aberrations as markers of disease severity in adoptive transfer experiments.